2005
DOI: 10.1523/jneurosci.0178-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Basal Forebrain Neurons Burst with Theta during Waking and Paradoxical Sleep

Abstract: It is known that acetylcholine can stimulate activation and promote plasticity in the cerebral cortex, yet it is not known how the cholinergic basal forebrain neurons, which release acetylcholine in the cortex, discharge in relation to natural cortical activity and sleep-wake states. By recording basal forebrain units in association with electroencephalographic activity across the sleep-wake cycle and labeling individual neurons with Neurobiotin for immunohistochemical identification, we show for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
332
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(356 citation statements)
references
References 45 publications
22
332
1
1
Order By: Relevance
“…Perhaps the most important (albeit still controversial in detail) role of ACh circuits in cortex and in hippocampus is in the regulation of theta rhythm oscillatory activity (Buzsaki, 2002;Calabresi et al, 2000;Cobb and Davies, 2005;Hasselmo, 2005;Lee et al, 2005). Thetafrequency band oscillations constitute a prominent network pattern in all mammals, including humans.…”
Section: Physiology Of Ach Circuits In Pfc and Hippocampusmentioning
confidence: 99%
“…Perhaps the most important (albeit still controversial in detail) role of ACh circuits in cortex and in hippocampus is in the regulation of theta rhythm oscillatory activity (Buzsaki, 2002;Calabresi et al, 2000;Cobb and Davies, 2005;Hasselmo, 2005;Lee et al, 2005). Thetafrequency band oscillations constitute a prominent network pattern in all mammals, including humans.…”
Section: Physiology Of Ach Circuits In Pfc and Hippocampusmentioning
confidence: 99%
“…Previous studies led to a general notion that cholinergic MS/DB are homogeneous, exhibiting similar firing behavior as described above (Griffith and Matthews, 1986, Griffith, 1988, Markram and Segal, 1990, Griffith et al, 1991, Brazhnik and Fox, 1997, Brazhnik and Fox, 1999. However, more recent work revealed that some basal forebrain cholinergic neurons do show bursting capabilities (Lee et al, 2005). This diversity in firing properties among basal forebrain cholinergic neurons may be related to connectivity.…”
mentioning
confidence: 91%
“…Such studies have almost exclusively focused on recording the activity of single neurons, often labelled according to cell type, and linking their firing patterns to the cortical EEG (Duque et al, 2000;Manns et al, 2000aManns et al, , 2000bHassani et al, 2009), wake/sleep regulation (Szymusiak et al, 2000;Lee et al, 2004Lee et al, , 2005, aspects of sensory stimulation (Lin and Nicolelis, 2008;Nguyen and Lin, 2014), and behavioral task performance (Thomson et al, 2014;Tingley et al, 2014Tingley et al, , 2015. Convergent evidence (Zaborszky et al, 1999;Yang et al, 2014;Xu et al, 2015) indicates that BF contains multiple interconnected and heterogeneous networks, which operate as an ensemble to modulate cortical state and play distinct roles during sleep and wakefulness.…”
Section: Introductionmentioning
confidence: 99%